Books that invite talk, wonder, and play - Kristo, Janice V.; McClure, Amy A. (Urbana, IL : National Council of Teachers of English, 1996)
Discusses the ways authors use language in a variety of genres to challenge and entertain young readers, explores books that promote cultural diversity, and includes essays by thirty-eight authors of Notable books in which they reflect on their own creative processes.
Includes bibliographical references (p. 309-323).
Booklist.
School Library Media Quarterly (A.A.A.L.).
Teacher Librarian.
Professional
Keywords: Children's literature, American -- History and criticism -- Theory, etc; Children's literature -- Authorship; Children -- Books and reading; Language arts; Children's literature -- History and criticism; Children's literature -- Technique; Children -- Books and reading; Language arts